"The little kingdom over which God made you queen": The gendered reorganization of a "modern" Arab home in turn-of-the-century Beirut - Halevi, Sharon; Zachs, Fruma (Hagar: Studies in Society and Culture, 2013)
Beginning in the second half of the nineteenth century, the major urban centers of Greater Syria underwent significant changes. Following the Tcmzimat. and provincial reforms of 1864 and the ensuing efforts at centralization and modernization, concerted efforts were made to rationalize the urban space and plan its expansion in advance. Historians have devoted considerable attention to these developments, to the emergence of various architectural styles (both public and private) and to the great impact these changes had on peoples’ lives. However, the reorganization of the interior domestic space, which went hand in hand with these changes, has barely been touched upon. In this article we examine the spatial implementation of an emerging modern Arab discourse of domesticity in the homes of the bourgeoisie in Beirut (the leading city of the region). Using a selection of newspaper articles, advice columns, novels and texts of public lectures (1880-1914), we trace the emerging contours of the home, paying close attention to the rearrangement of rooms and their decorations, the new consumer items which entered the home and the psychological impact these changes were intended to generate among the residents. Last, but not least, we look at the person put in charge of the reorganization of the home, the wife and mother.